2012
DOI: 10.1111/j.1752-699x.2012.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of cytologic analysis of bronchial washings in lung cancer on the basis of bronchoscopic appearance

Abstract: The combination of forceps biopsy and washing cytologic analysis offers a better diagnostic yield than biopsy alone in diagnosing lung cancer. Both procedures should be performed during bronchoscopy even if no endobronchial lesion is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…10,11 However Lee GD et al and Shagufta TM et al obtained good diagnostic yield with BW which was at variance with this study. 9,12 In current study, in comparison to BW, BB gave a higher number of TP and TN and lesser number of FN cases, showing superiority of BB over BW. High percentage of FN with BW could be because of BW technique relies mainly on cells exfoliated from malignant lesion in bronchial epithelium and the adequacy of its samples depend on several factors especially preservation of morphology of cytological material obtained, degree of differentiation of malignant growth and technical skill of pulmonologist in performing washing in retrieving wash fluid.…”
Section: Discussionsupporting
confidence: 47%
“…10,11 However Lee GD et al and Shagufta TM et al obtained good diagnostic yield with BW which was at variance with this study. 9,12 In current study, in comparison to BW, BB gave a higher number of TP and TN and lesser number of FN cases, showing superiority of BB over BW. High percentage of FN with BW could be because of BW technique relies mainly on cells exfoliated from malignant lesion in bronchial epithelium and the adequacy of its samples depend on several factors especially preservation of morphology of cytological material obtained, degree of differentiation of malignant growth and technical skill of pulmonologist in performing washing in retrieving wash fluid.…”
Section: Discussionsupporting
confidence: 47%
“…Similar results were reported by other studies which concluded that for endoscopically visible tumors, the diagnostic yield of BW does not differ whether performed before or after BB and biopsy. [228232233234] However, a prospective randomized trial by Hou et al . [235] concluded that in endobronchial exophytic tumors, prebiopsy brushing appears to be superior to postbiopsy brushing.…”
Section: Bronchoscopic Samplingmentioning
confidence: 99%
“…Rivera et al 9 in review of 34 studies for of flexible bronchoscopic diagnostic procedures for peripheral lung carcinomas concluded sensitivity of BAL as 43%, in this review highest sensitivity recorded was 65% and lowest being 12%, BAL cytology shows increased yield with subsequent sampling, which was also documented by previous studies. [10][11][12] Variation in sensitivity in our study and other studies were due to following reasons 10,11,13 -1. Site of lesion.…”
Section: Discussionmentioning
confidence: 73%